Imaging Nasal Obstruction: An Objective Evaluation for a Subjective Complaint - Abreu, Vasco R.L.S.; Xavier, João A. (Facial Plastic Surgery, 2024)
Nasal obstruction (NO) is a common clinical symptom characterized by a subjective sensation of insufficient airflow through the nasal cavity and may result from various factors, including changes in nasal anatomy, inflammatory conditions, tumoral lesions, and other etiologies. While a thorough medical history and physical examination can often identify its cause, imaging is usually necessary to fully understand the problem. Computed tomography (CT) is the primary imaging modality used to evaluate the nasal cavity and paranasal sinuses, allowing for the identification of potential causes and structural abnormalities. However, when soft tissue characterization is required, magnetic resonance imaging (MRI) is also useful. Understanding the anatomical and pathological basis of NO is crucial for accurate diagnosis and appropriate management. Imaging techniques provide valuable information for identifying the underlying causes of NO and guiding treatment decisions. This article reviews the normal anatomy of the nasal cavity and adjacent paranasal sinuses as well as the several conditions that may affect breathing comfort (tumors, inflammatory diseases, bony and cartilaginous anatomical variants, and “nonobstructive” mucosal thickenings), showing their normal presentation on CT and MRI.
Keywords: nasal obstruction; CT; MRI